A Vesicle‐to‐Worm Transition Provides a New High‐Temperature Oil Thickening Mechanism. Issue 7 (10th January 2017) - Derry, Matthew J.; Mykhaylyk, Oleksandr O.; Armes, Steven P.
Abstract: Diblock copolymer vesicles are prepared via RAFT dispersion polymerization directly in mineral oil. Such vesicles undergo a vesicle‐to‐worm transition on heating to 150 °C, as judged by TEM and SAXS. Variable‐temperature 1 H NMR spectroscopy indicates that this transition is the result of surface plasticization of the membrane‐forming block by hot solvent, effectively increasing the volume fraction of the stabilizer block and so reducing the packing parameter for the copolymer chains. The rheological behavior of a 10 % w/w copolymer dispersion in mineral oil is strongly temperature‐dependent: the storage modulus increases by five orders of magnitude on heating above the critical gelation temperature of 135 °C, as the non‐interacting vesicles are converted into weakly interacting worms. SAXS studies indicate that, on average, three worms are formed per vesicle. Such vesicle‐to‐worm transitions offer an interesting new mechanism for the high‐temperature thickening of oils. Abstract : A vesicle‐to‐worm transition occurs on heating poly(stearyl methacrylate)13 ‐poly(benzyl methacrylate)96 block copolymer vesicles in mineral oil to provide a new high‐temperature oil‐thickening mechanism.